INFLUENCE SITUATIONAL LEADERSHIP, EMPLOYEE SATISFACTION, ORGANIZATIONAL CULTURE, ON EMPLOYEE PERFORMANCE AT JEMBER PULMONARY HOSPITAL WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Fawaid, Nurul; Satoto , Eko Budi; Herlambang, Toni (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the influence of situational leadership, employee satisfaction, and organizational culture on employee performance at Jember Lung Hospital, with work motivation as an intervening variable. Method: This research was conducted using quantitative research methods. The study utilized SEM analysis tools, with a total sample consisting of all members of the population, amounting to 137 employees. The sampling method used was the saturated sample method. Results: The results indicate that situational leadership does not directly affect motivation. However, employee satisfaction and organizational culture have a significant effect on motivation, and motivation has a significant effect on performance. Indirectly, motivation mediates the influence of situational leadership on employee performance at Jember Lung Hospital. Meanwhile, motivation does not mediate the effect of employee satisfaction and organizational culture on employee performance. Novelty: This study provides insights into the indirect role of motivation in mediating the relationship between situational leadership and employee performance, highlighting its specific impact within the context of Jember Lung Hospital.